Pneumonias in immunocompromised patients: improvement of treatment using the immunomodulator - Borisova, Inna; Pertseva, Tetyana (ScienceRise: Medical Science, 2017)
Aim of research: to optimize the approach to the treatment of pneumonias in patients on the background of acute leucosis from positions of immunoresistance based on using disodium glutamyl-cysteinile-glycine by the method of extracorporal pharmacotherapy. Materials and methods. Research group – 39 patients with pneumonia on the background of acute leucosis, who underwent the treatment according to the form and stage of the disease on the base of the hematological center “MI city multi-profile clinical hospital No. 4» Dnipro city, 2015–2016. Mean age of patients 31,5±6,5 years, 11 women and 38 men. Patients of the main group were additionally administered with disodium glutamyl-cysteinile-glycine in 2 ml of 3 % solution (60 mg) i/v No. 5 each second day. The parameters of the immune response were studied: Т and В-lymphocytes and their subpopulational composition (CD3+, CD4+, CD8+, CD19+, CD16+, CD56+) by the method of flow laser cytoflourometry (BeckmanCoulter–USA). There were additionally determined; immunoregulatory index, leuco T-cellular index, leuco B-cellular index and index of leucocytes activation; phagocytosis state was assessed by the parameters: phagocytic number, phagocytic indicator, NBT-tests. The state of humoral immunity was assessed by levels of immunoglobulins of classes A, M and G by the method of immunoturbidimetry (BeckmanCoulter–USA). Results. The analysis of parameters of cellular and humoral immunity of patients with pneumonias on the background of AL by the improved method of treatment of pneumonia using the immunomodeling preparation disodium glutamyl-cysteinile-glycine proved the positive influence on the immune reactivity of patients’ organism, manifested by the reliable increase of the relative quantity of the pool of T-helpers (CD4+), NК-cells, increase of immunoregulatory index, PI, PN and increase of humoral immunity indices. Conclusions. The improved method of pneumonia treatment on the background of AL using the immunomodeling preparation disodium glutamyl-cysteinile-glycine by ECPT method proved the positive influence of the immune reactivity of patients’ organism, manifested by the reliable activation of phagocytosis and anti-infectious protection, manifested by the more expressed effect of pneumonia treatment: improvement of the clinical course of disease; decrease of the prognosticated number of ABT days and earlier return to the program treatment of AL. The obtained effects of the improved method of pneumonia treatment in patients with acute leucosis at using the immunomodeling preparation disodium glutamyl-cysteinile-glycine by ECPT method proves the pathogenetic validity of the possibility of optimization of pneumonia treatment from positions of immunoresistance